Correlation of 18‐fluorodeoxyglucose uptake values on PET–CT scan with histological prognostic markers in breast cancer. Issue 2 (7th July 2022) - Muduly, Dillip Kumar; Ephraim, Rebba; Sultania, Mahesh; Ray, Sudatta; Bhoriwal, Sandeep; Pathak, Mona; Kar, Madhabananda
Abstract: Background: Positron emission tomography–computed tomography (PET‐CT) scan utilizes 18‐fluorodeoxyglucose (18‐FDG), based on the principle of higher glycolytic activity and reduced glucose‐6‐phosphatase levels in cancer cells. This imaging modality is usually advised in the metastatic evaluation of stage III breast cancer patients. The correlation of maximum standard uptake values of primary lesion with different pathological and molecular markers has not been studied extensively. Methods: Retrospective analysis of the data was performed from our prospectively maintained breast cancer database. All the patients who had undergone 18‐FDG PET–CT scan at initial evaluation for staging between June 2017 and April 2020 were included in the study. One‐way ANOVA test or Student's t ‐test as appropriate was performed to assess the difference of means in maximum standard uptake values (SUVmax) of the primary lesion and axillary nodes with clinical stage, histological grade, molecular subtype. Bonferroni post hoc test was also applied. Results: Out of 388 patients in the breast cancer database, 45 patients met inclusion criteria. There was a significant correlation of molecular subtype ( p  = 0.029) with SUVmax of the primary lesion. Higher primary SUVmax was associated with higher T stage ( p  = 0.01) and higher histological grade ( p  = 0.06). In each molecular subtype, there was an increase in mean SUVmax of the primary lesion with increasing histological grade and vice versa. Conclusions: SUVmax of the primary lesion in breast cancer patients reflects tumor biology. Higher SUVmax can predict patients with triple‐negative breast cancers and higher grades in primary tumors. However, further large‐scale validatory studies are essential. Abstract : SUVmax of the primary lesion in breast cancer ⤍ predicts probable molecular subtype Triple‐negative disease and higher histological grades show higher SUVmax ⤍ Reflects its potency to assess tumour biology Signifies the prognostic role of PET scan